Some aspects of the computational complexity in the design of islanded microgrids, design and analysis of blackstart sequences for a notional microgrid - Natarajan, Sudarshan Ananda, author; Suryanarayanan, Siddharth, advisor; Rajopadhye, Sanjay, advisor; Zimmerle, Dan, committee member; Putkaradze, Vakhtang, committee member (Colorado State University. Libraries, 2012)
The US grid represents more than $1 trillion in assets and serves over 100 million customers. But the grid is an aging system, and was built as centralized system architecture. The Title XIII of the Energy Independence and Security Act of 2007 outlined the 'Smart Grid Initiative' (SGI) as an official policy for modernization of the United States electricity transmission and distribution system to improve reliability and upgrade infrastructure to meet the ever increasing demand in electricity. The distribution feeder is the final link between the generation units and the end user. Distribution networks were traditionally designed in a radial topology since such configurations resulted in simpler protective schemes. More recently, there has been a renewed focus on distribution feeder reconfiguration. Reconfiguration at the distribution level can be achieved by the use of switches and sectionalizers. This enables portions of the distribution network to be reconfigured dynamically to improve reliability, hence enabling control on the topological structure of the distribution feeder. A related feature is the microgrid, or an islanded distributed resource (DR). The IEEE 1547.4 Standard on 'The guide for design, operation and integration of DR island systems with electric power supply' defines a microgrid as an electric power system that has the following properties: • a local distributed resource and load • the ability to disconnect from and parallel with the area electric power supply • include the local electric power supply and portions of area electric power supply A microgrid is capable of disconnecting from the main grid, on sensing a disturbance on the main grid, to maintain reliable supply of electricity to the constituent end-user loads. In this work, the computational complexity of the design of islanded microgrids by the optimal addition of network feeders in a legacy radial electric distribution system is identified, and a technique to accelerate the process of finding Pareto optimal solutions to the problem is provided. The next part of this thesis models a notional microgrid with blackstart capabilities. Microgrids that cannot continue uninterrupted supply to all local loads on disconnection from main grid are required to follow a sequence for startup which is known as the blackstart sequence. In this work, the various generation resources in the notional microgrid are studied and a blackstart sequence is engineered.
Keywords: distribution feeder reconfiguration; smart grid; power systems; microgrid